Diversity of insect trypanosomatids assessed from the spliced leader RNA and 5S rRNA genes and intergenic regions - Podlipaev, Sergei A; Sturm, Nancy R; Fiala, Ivan; Fernandes, Octavio; Westenberger, Scott J; Dollet, Michel; Campbell, David A; Lukes, Julius (The Journal of eukaryotic microbiology, 2004)
We have determined the sequences of 5S rRNA and spliced leader (SL) RNA genes, and adjacent intergenic regions for representatives of all known trypanosomatid genera parasitizing insects. The genetic loci have been analyzed separately as well as by a combined approach. Several isolates, assigned by morphology to different genera (Leptomonas spp., Blastocrithidia spp.), seem to belong to a single species with an unexpectedly wide host and geographical range. An unnamed trypanosomatid isolated from rats in Egypt was found to belong to the genus Herpetomonas, so far associated with insect hosts only. It is closely related to Herpetomonas ztiplika, a parasite of a blood-sucking biting midge. Apparently several different trypanosomatid species can infect one insect species, as exemplified by Leptomonas sp. PL and Wallaceina sp. Wsd, which were isolated from different specimens of Salda littoralis on the same locality and day. However, since the same species of Leptomonas was obtained from insect hosts belonging to different genera, some insect trypanosomatids may have low host specificity. Our data revealed additional discrepancies between molecular phylogenetic data and cell morphology, rendering current trypanosomatid taxonomy unreliable.
Keywords: RNA, Ribosomal, 5S; hmyz; Phylogeny; DNA, Intergenic; Molecular Sequence Data; RNA, Protozoan; molekulární sekvence - údaje; RNA se sestřihovou vedoucí sekvencí; protozoální geny; Genes, Protozoan; zvířata; RNA ribozomální 5S; Insecta; genetická variace; Genetic Variation; fylogeneze; RNA protozoální; Trypanosomatina; RNA, Spliced Leader; Animals; intergenová DNA